1983
DOI: 10.1002/ijc.2910310510
|View full text |Cite
|
Sign up to set email alerts
|

Biological characterization and clinical applications of a monoclonal antibody recognizing an antigen restricted to neuroectodermal tissues

Abstract: The monoclonal antibody UJ13A was raised following immunization of mice with human foetal brain and subsequent somatic cell hyridization of spleen cells with the mouse myeloma cell line P3-X63-AG8-653. The antibody is of the IgG1 subclass and has been shown by indirect immunofluorescence studies on normal foetal, paediatric and adult tissues to selectively bind to most tissues of neuroectodermal origin. Many tumours of neural origin also express the UJ13A antigen and the reagent can be used to distinguish prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

1986
1986
1996
1996

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(34 citation statements)
references
References 12 publications
0
34
0
Order By: Relevance
“…Markers selected for study include: NSE, an isoenzyme of the glycolytic enzyme enolase which has been identified as a marker for SCLC and other NE tumours (Schmechl et al, 1978;Marangos et al, 1982); creatine kinase BB (CK-BB) found in large amounts in the brain, gastro-intestinal tract and SCLC ; chromogranin-A, a protein which stabilises the intragranular matrix of neurosecretory/ dense core granules (DCG) (Bishop et al, 1988); protein gene product 9.5 (PGP 9.5), a ubiquinated protein (Wilkinson et al, 1989) reported to be present in nerves, neuroendocrine tissues and associated benign and malignant tumours ; bombesin-like peptides and neurotensin, hormones often elaborated by SCLC and other neuroendocrine tumours (Moody et al, 1981;Hamid et al, 1987); synaptophysin, a membrane protein isolated from presynaptic vesicles of bovine neurones, and reported to be present in the normal neural and neuroendocrine tissues and tumours associated with them (Gould et al, 1986); and finally we have examined the expression of the cell surface protein NCAM (neural cell adhesion molecule), which is recognised by the monoclonal antibody UJ-13A (Patel et al, 1989;Allan et al, 1983 (Hermanek et al, 1987 Normal tissues A range of normal tissues were included in the study to assess antibody specificity for neuroendocrine tissues. These included pancreas, small and large bowel, testis, thyroid, pituitary, adrenal gland, adult and foetal lung, bronchus, kidney, muscle, brain, spinal cord, spleen and lymph node which were obtained from surgically resected specimens and fresh post-mortem cases.…”
mentioning
confidence: 99%
“…Markers selected for study include: NSE, an isoenzyme of the glycolytic enzyme enolase which has been identified as a marker for SCLC and other NE tumours (Schmechl et al, 1978;Marangos et al, 1982); creatine kinase BB (CK-BB) found in large amounts in the brain, gastro-intestinal tract and SCLC ; chromogranin-A, a protein which stabilises the intragranular matrix of neurosecretory/ dense core granules (DCG) (Bishop et al, 1988); protein gene product 9.5 (PGP 9.5), a ubiquinated protein (Wilkinson et al, 1989) reported to be present in nerves, neuroendocrine tissues and associated benign and malignant tumours ; bombesin-like peptides and neurotensin, hormones often elaborated by SCLC and other neuroendocrine tumours (Moody et al, 1981;Hamid et al, 1987); synaptophysin, a membrane protein isolated from presynaptic vesicles of bovine neurones, and reported to be present in the normal neural and neuroendocrine tissues and tumours associated with them (Gould et al, 1986); and finally we have examined the expression of the cell surface protein NCAM (neural cell adhesion molecule), which is recognised by the monoclonal antibody UJ-13A (Patel et al, 1989;Allan et al, 1983 (Hermanek et al, 1987 Normal tissues A range of normal tissues were included in the study to assess antibody specificity for neuroendocrine tissues. These included pancreas, small and large bowel, testis, thyroid, pituitary, adrenal gland, adult and foetal lung, bronchus, kidney, muscle, brain, spinal cord, spleen and lymph node which were obtained from surgically resected specimens and fresh post-mortem cases.…”
mentioning
confidence: 99%
“…The 2 monoclonal antibodies UJ13A and HSAN 1-2 bind to neuroblastoma; they were kindly provided by J.T. Kemshead (Allan et al, 1983;Kenshead et al, 1983) and L.P. Reynolds (Reynolds et al, 1982) respectively. In BM taken from healthy donors, Table I).…”
Section: Methodsmentioning
confidence: 99%
“…These transplants can be freed of malignant cells (purging) when required by detection of minimal residual disease. Neuroblastoma is a disease with focal BM involvement and multiple biopsies would be more appropriate than aspirates for detecting low levels of tumour cells (Franklin & Pritchard, 1983;Bostrom et al, 1985 which selectively bind to cells of neuroectodermal origin have also been developed (Reynolds et al, 1982;Kemshead et al, 1983;Allan et al, 1983;Donner et al, 1985). Two of these antibodies were used in an indirect immunofluorescence assay to confirm and extend the detection of neuroblastoma cells in suspensions of BM cells.…”
mentioning
confidence: 99%
“…To determine the degree of microaggregates and free iodine in the radiolabelled protein preparations, they were subjected to Sephacyl S300 column chromatography and precipitation with 10% trichloroaceric acid. In the first five administrations, immunological activity was assessed by an indirect immunofluoresence assay (Allan et al, 1983). Due to the insensitivity of this technique, later preparations were assayed for the proportion of immunoreactive radiolabelled antibody in a direct radioimmunoassay under conditions of antigen excess (Zalutsky et al, 1989 Table I. Antibody preparation Antibody preparations were relatively free from microaggregates (mean value 1%, range 0.5%; n = 13), and free iodine (mean value 4.1%; range 1-13%; n = 14).…”
Section: Patient Selectionmentioning
confidence: 99%